The Influential Role of the Senate VS the Declining Role of the House of Lords - Ammari, Boulifa, Hachimi khaled; Touati Ahmed, Abdelhadi (Univesity of El-Oued, 2022)
This thesis studies the chronological development of the Senate and the House of Lords in both the United States of America and the United Kingdom. Its aim is to point out the advantages and the disadvantages that both of the houses have gradually obtained over the years. Its main objective is to explain to the researchers about the major causes that led one house to rise up and led the other to fall down, as well as to compare their roles between the past and recent years. This study adopts historic, descriptive, and analytical method where the researchers reviewed various reliable sources. The findings of this study revealed that the Senate was given more powers by the framers of the constitution to distinguish them from the people and their opinions about the government actions, while the House of Lords powers eroded by the Commons that has inclinations to the people in their decisions to make, thus, the roles of the House of Lords differ from the roles of the Senate on many scales due to past distribution of power of both houses. تدرس هذه المذكرة التطور الزمني لمجلس الشيوخ ومجلس اللوردات في كل من الولايات المتحدة الأمريكية والمملكة المتحدة. هدفه هو الإشارة إلى المزايا والعيوب التي حصل عليها كلا المنزلين تدريجياً على مر السنين. هدفها الأساسي هو أن تشرح للباحثين الأسباب الرئيسية التي أدت إلى قيام أحد المنازل وقاد الآخر إلى الانهيار ، وكذلك مقارنة أدوارهم بين السنوات الماضية والأخيرة. تتبنى هذه الدراسة المنهج التاريخي والوصفي والتحليلي حيث قام الباحثون بمراجعة مختلف المصادر الموثوقة. كشفت نتائج هذه الدراسة أن مجلس الشيوخ قد منح المزيد من الصلاحيات من قبل واضعي الدستور لتمييزهم عن الناس وآرائهم حول تصرفات الحكومة ، بينما تآكلت سلطات مجلس اللوردات من قبل مجلس العموم الذي كان له ميول للشعب في وبالتالي ، تختلف قراراتهم في اتخاذ أدوار مجلس اللوردات عن أدوار مجلس الشيوخ في العديد من المستويات بسبب التوزيع السابق للسلطة لكلا المجلسين
Keywords: United States, United Kingdom, Congress, Parliament, House of Lords, The S nate, Role of the House of Lords, Role of the Senate.; الولايات المتحدة ، المملكة المتحدة ، الكونغرس ، البرلمان ، مجلس الأعيان ، مجلس الشيوخ ، دور مجلس لأعيان ، دور مجلس الشيوخ